Energy Generation from Osmotic Pressure Difference Between the Low and High Salinity Water by Pressure Retarded Osmosis - Wang, Xu; Huang, Zhongmai; Li, Lei; Huang, Shusheng; Yu, Eileen Hao; Scott, Keith (Journal of Technology Innovations in Renewable Energy, 2013)
Osmosis is a natural phenomenon and exists widely from the salinity gradient between sea water and fresh water. This green energy can be captured using pressure retarded osmosis (PRO). A potential energy of 2.5 terawatts is available globally from rivers flowing into the sea. Membrane is the key component and it has been the main limitation for this technique. The most challenging problem is the internal concentration polarization (ICP) which reduces the water flux by up to 80 %. This paper reviews most critical and recent publications on membrane fabrication (e.g. composite membrane, hollow fibber membrane). Summary and perspectives will be given in order to prepare high performance membranes.